2019
DOI: 10.1364/boe.10.005431
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous label-free autofluorescence and multi-harmonic imaging reveals in vivo structural and metabolic changes in murine skin

Abstract: Simultaneous quantification of multifarious cellular metabolites and the extracellular matrix in vivo has been long sought. Simultaneous label-free autofluorescence and multi-harmonic (SLAM) microscopy has achieved simultaneous four-channel nonlinear imaging to study tissue structure and metabolism. In this study, we implemented two laser systems and directly compared SLAM microscopy with conventional two-photon microscopy for in vivo imaging. We found that three-photon imaging of adenine dinucleotide (phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…EVs were isolated from cell conditioned media using differential ultracentrifugation, embedded in a 0.2% (w/vol) agarose gel, and imaged using a previously described custom laser scanning multiphoton setup with FLIM capabilities 34 . The mean fluorescence lifetime, τ , of each EV was calculated using the phasor approach for FLIM analysis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs were isolated from cell conditioned media using differential ultracentrifugation, embedded in a 0.2% (w/vol) agarose gel, and imaged using a previously described custom laser scanning multiphoton setup with FLIM capabilities 34 . The mean fluorescence lifetime, τ , of each EV was calculated using the phasor approach for FLIM analysis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EV and cell samples were imaged at room temperature (about 25 °C) using a previously described custom laser scanning multiphoton setup with FLIM capabilities 34 . The glass bottom imaging dishes allow for illumination and detection from below the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autofluorescence from the cell is typically from oxidative chain respiratory proteins NADH and FAD and high levels of NADH have been associated with glycolysis or regions of hypoxia. 37,38 Bower et al, have demonstrated that incorporation of fluorescence lifetime imaging microscopy (FLIM) is able to separate free and bound NADH in living samples, and developed a video rate FLIM system which could add information on metabolic activity to the images. 39 6.2 Imaging in the C-H region 6.2.1 DNA Imaging.…”
Section: Second Harmonic Generation and Other Non-linear Modalitiesmentioning
confidence: 99%
“…As significant recent milestones along this route, 3PEF imaging has been extended to neuronal activity studies deep in intact mouse brain, [12] wide-field three-photon optogenetic stimulation, [13] and brain structure and function detection through an intact skull, [14] as well as 3PEF lightsheet microscopy. [15] In most recent studies, [16,17] 3PEF has been successfully combined with THG to provide a powerful tool for a multimodal optical imaging of skin and diagnostics of its pathologies. Here, we extend this approach and demonstrate its potential for imaging and understanding a vast variety of biological systems and settings, ranging from HeLa to brain cells.…”
Section: Introductionmentioning
confidence: 99%